The Pivotal Dimensions of Employee Job Satisfaction in Fostering Organizational Commitment at the Medan City Tourism Agency - Muhammad Taufiq; Hasrudy Tanjung (LPPM Institut Teknologi dan Sains Mandala, 2022)
This research examines the multidimensional structural relationship between job satisfaction and organizational commitment among employees at the Medan Tourism Agency, North Sumatra. Utilizing a quantitative approach with a correlational design, data were gathered through a purposive sampling technique, resulting in 55 valid respondents who are civil servants and contract employees with a minimum of one year of tenure. Data collection was carried out intensively over one month using structured questionnaires. The collected data were analyzed using multiple linear regression analysis. The result reveals that all job satisfaction dimensions collectively exert a significant effect on organizational commitment, explaining 28.8% of the total variance. However, the partial analysis unveils a unique single-path significance phenomenon; only satisfaction with the work itself demonstrates a positive and significant effect on organizational commitment. Conversely, extrinsic factors such as pay, supervision, co-workers, and promotion opportunities show no significant effects, acting merely as hygiene factors. These findings theoretically reinforce Herzberg’s Two-Factor Theory within public bureaucracy, demonstrating that intrinsic job content drives deeper institutional loyalty than job context. Practically, the management should focus on job enrichment strategies, creative autonomy, and enhancing supervisory support to sustain and optimize long-term organizational commitment.